Слов’янські прикраси раннього середньовіччя із Полтавського Посулля: нові знахідки - Володарець-Урбанович, Я.В.; Сидоренко, О.В. (Археологія і давня історія України, 2021)
У статті розглянуто знахідки прикрас епохи
раннього середньовіччя, які були виявлені з 2011 по
2016 рр. у полтавському Посуллі під час обстежень
археологічних пам’яток. Знахідки представлені фібулами, деталями намиста, браслетами та деталями поясних гарнітур. Article presents jewelry findings from Sula basin in
the Poltava region. They were discovered between 2011
and 2016 on Slavic monuments of the early Middle
Ages — Penkivka culture and Sakhnivka horizon. Jewelry
findings find analogies among the Dnieper treasures
by Martynivka and jewelry of Pastyrske hillfort.
Two fibulae (radiate-headed and anthropozoomorphic)
and small bell were detected on settlement
Khyttsi tract Shemberovo (fig. 1; 2). Fragment of radiate-
headed brooch (fig. 1: 1; 2: 1) may belong to fibulae
with a border of birds’ heads. Small bell (fig. 1: 2; 2:
2) decorated of two mortise lines finds wide analogies
among Slavic antiquities (treasures of the Martynivka
and Kolochyn culture) and early medieval cemeteries
of the Crimea: Skaliste and Luchiste. Radiate-headed
brooch and small bell date to the second half of the
6th—7th century.
Anthropozoomorphic brooch (fig. 1: 3; 2: 3) belongs
to the jewelry made on the Pastyrske hillfort. The
spread of such fibulae indicates the migration of a
small part of the inhabitants of the Pastyrske hillfort
or with trade and exchange relations. Fibula belongs to
the Sakhnivka cultural and chronological horizon and
dates from the second half of the 7th — the first half of
the 8th century.
Other finds of were found on settlement Vovchyk
tract Rudka (fig. 9; 10). Products of Penkivka culture
are: fragment of radiate-headed brooch, five fragments
of bracelets and six heraldic belt set details (fig. 9: 1—
12; 10: 1—12).
Lunar-shaped item (fig. 9: 17; 10: 17) dates from period
of Kievan Rus. Two buckles belong to the jewelry
of the late Middle Ages or Modern times (fig. 9: 13, 14;
10: 13, 14).
The new findings enrich the understanding of typological
diversity, evolution and their ranges and help
to identify areas of trade and economic ties, migration
routes, to identify certain cultural and historical areas.